(untitled) (Research, Society and Development, 2022)
Dentin sensitivity is the main side effect in cases of tooth whitening, and although there are a variety of products formulated for its management, with different degrees of effectiveness, there is still no universally accepted therapy to alleviate the symptoms of this sensitivity. Thus, the objective of this work is to present the clinical strategies used to reduce sensitivity in cases of tooth whitening. This is a descriptive study of the integrative literature review type, carried out through the following databases: PubMed, SciELO and VHL. For this review, articles available in full in Portuguese and English were included, and theses, monographs, course conclusion works, books and other literature reviews were excluded. The descriptors used were: Tooth Bleaching; Dentin Sensitivity; Dentin Desensitizing Agents, organized into a search key combination using the Boolean operator “AND”. A total of 114 articles were found, of which, after excluding those that did not meet the inclusion criteria and were not relevant to the theme, 7 articles were selected for the construction of the review. Despite the divergent opinions present in the literature, it is noted that the use of fluorides associated with products containing bioactives, such as argine, potassium nitrate and calcium phosphate, have better results in the control of dentin sensitivity due to their natural actions of tubular occlusion and formation of a protective layer on tooth enamel, hus being a safer and more used option.